Screening of fungal azole resistance in different environmental samples - Pena, Pedro (2020)
Fungi are responsible for skin diseases, infections of the lung and other organs, and bloodstream infections due to their presence in several environments such as in agriculture. Antimicrobial resistance has been described as a product of healthcare and agricultural overuse of azoles to inhibit fungal growth. The aim of this review article is to assess methodologies for fungi sampling and for the screening of azole resistance in environmental samples. The search was carried out in three search engines: PubMed, Scopus, and Web of Science (WoS). The Search terms in all databases were “fungal resistance in environmental samples”. After applying the inclusion criteria, the number of analyzed articles was 18 out of 71. The azole resistance tests were performed, in non-hospital environment samples, using mainly the EUCAST and CLSI M38-A2 broth microdilution methods. The most reported azole-resistant fungi were Aspergillus fumigatus, and the most common azoles used to perform the susceptibility tests were itraconazole, voriconazole, and posaconazole. Samples of air, water, and soil were considered, and the most found and studied fungi as Aspergillus fumigatus. This fungus is known to be an allergenic and mycotoxin producer with severe health consequences. It represents a concern for public health for its increasingly described resistance to the three azoles most used in clinical practice: itraconazole, voriconazole, and posaconazole. It is suggested the assessment of fungi in other occupational and indoor environments, as well as of their resistance for a better characterization of these environments. It is also suggested the use of complementary sampling methods for the fungal assessment.